Effect of Rehabilitation Robot Combined with Upper Limb Rehabilitation Training on Hemiplegic Patients in Recovery Stage of Stroke - LI Yuqi; HUANG Guozhi; LU Pengcheng; HE Longlong; HUANG Wenhao; HUANG Chuhong; ZENG Qing (康复学报)
Objective: To observe the effect of upper limb rehabilitation robot combined with upper limb rehabilitation training on motor function of upper extremity of hemiplegic patients in recovery stage of stroke.MethodsA total of 40 hemiplegic patients in recovery stage of stroke who were treated in the Zhujiang Hospital of Southern Medical University from October 2018 to January 2020, which were randomly divided into the control group and the observation group according to the random number table method, with 20 cases in each group. Both groups received basic medication and conventional rehabilitation therapy (including good limb position, active and passive joint movement, sitting and standing balance training, walking function training, assistive device use training, speech and swallowing therapy, conventional physical therapy, etc.). The control group received upper limb rehabilitation training on the basis of basic medication and conventional rehabilitation therapy, 60 minutes a time, once a day, seven days a week, continuous treatment for two weeks. The observation group received upper limb rehabilitation robot training on the basis of the control group, upper limb rehabilitation training for 30 minutes a time, upper limb robot rehabilitation training for 30 minutes a time, once a day, seven days a week, continuous treatment for two weeks. Before and after treatment, the Fugl-Meyer assessment-upper limb (FMA-UL) was used to evaluate the motor function of upper extremity, including the FMA shoulder and elbow (FMA-SE) score and the FMA wrist and hand (FMA-WH) score; the Barthel index (BI) was used to evaluate activities of daily living; the root mean square (RMS) and integral electromyography (iEMG) values of the biceps, triceps, deltoid of anterior and middle fiber of the affected upper limbs of the subjects during maximal isometric contraction were measured by surface electromyography to assess muscle activation and synchronization of motor recruitment of the upper limbs.ResultsA total of 38 hemiplegia patients in the recovery stage of stroke completed the whole course of treatment. Compared with before treatment, FMA-UL score, FMA-SE score, FMA-WH score, BI score, RMS values of biceps, triceps, deltoid of anterior and middle fiber, and iEMG values of the both groups after treatment were significantly higher, with statistically significant differences (P<0.05). Compared with the control group, the FMA-UL score, FMA-SE score, BI scores, triceps RMS value, deltoid of middle fiber RMS value and iEMG value of observation group were significantly higher, with statistically significant differences (P<0.05).ConclusionUpper limb rehabilitation robot combined with upper limb rehabilitation training can effectively improve motor function of upper limb, muscle activation and motor unit recruitment synchronization of hemiplegic upper limb, and improve the activities of daily living of hemiplegic patients in recovery stage of stroke, which is worthy of clinical promotion.